سمات النص القانوني وترجمته من الإنجليزية إلى العربية - الأمين ســعدية (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تحظى ترجمة النصوص القانونية باهتمام متزايد في مجال الترجمة ممارسة وتنظيراً، وذلك لكون النص القانوني مستنداً مهماً يحتوي على مواد وأحكام تنظم العلاقات بين الأطراف - أفراداً كانوا أم شركات أم دولاً، فيوضح ما لكل طرف من حقوق وما عليه من واجبات. ونسبة لأهمية هذه المواد وما تشير إليه من مفاهيم قانونية، وجب أن ترد في النصوص بعبارات واضحة لا مجال فيها لأي لبس أو غموض أو تفسيرات متضاربة. لهذا السبب فإن النصوص القانونية يصوغها المختصون بالقانون وفق طرائق معينة، بعبارات راسخة ثابتة على مر السنين، استعملها من سبقهم في المهنة، واستمروا في استخدامها بعد أن تأكدوا أنها تفضي مباشرة إلى المفاهيم المعنية. وهكذا، فإن المصطلح والتعبير القانوني الذي لا يعرفه ولا يفهمه تقريباً سوى المختصين الذين تدربوا عليه خلال دراستهم، أو نقلوه من الكتب المراجع، إنّ ذلك المصطلح قد تطور فأصبح لغة متكاملة قوامها مجموعة من العبارات المسكوكة والقوالب اللغوية الجاهزة الجامدة التي لا ينفصل شكلها عن مضمونها القانوني. هذه السمات التي ينفرد بها النص القانوني تؤثر بدورها في عملية ترجمته فتحدد الطرائق والأساليب التي يجب على المترجم إتباعها، كما تضيف مزيدا من المعارف والمهارات المطلوبة للقيام بكل واحدة من خطوتي العملية: فهم النص المصدر، وصياغة النص الهدف. فالخطوة الأولى تقتضي معرفة معمقة باللغة المصدر، خصوصا النوعية المكتوبة منها، بأسلوبها الرسمي في أقصى درجاته، كما تتطلب مقدرة تحليلية فائقة تتيح التوصل إلى معنى النص بالرغم من نسيجه المعقد بسبب الجمل الطويلة والمفردات والعبارات النادرة التي تبتعد ما أمكن ذلك عن لغة الاستخدام اليومي. أما مرحلة الصياغة فتحتاج لإتقان التعبير بلغة الهدف إتقاناً تاماً، خصوصا الأسلوب الرسمي التقني منها، كما تقتضي المقدرة على البحث في النصوص الموازية لإيجاد التعبير القانوني السليم بقوالبه الجاهزة وأنماطه المتكررة التي اعتاد المختصون على استخدامها في كل نوعية من نوعيات النصوص القانونية. Translating legal texts attracts more and more attention in the field of translation, whether in the practice of the profession or at the theoretical level. This growing interest arises from the importance of the text being a document containing articles of law to govern the relationships between parties –individuals, companies or states, by conferring rights and imposing obligations. Due to the importance of these articles, together with the legal concepts they convey, they need to be stated in the texts with the maximum degree of clarity, avoiding any ambiguity that may lead to miscomprehension or give rise to different interpretations. For this reason, the legal texts are usually drafted in a specific manner by law professionals, who use fixed formulaic expressions which have been tried and tested over the years by their predecessors, and found suitable for directly conveying the desired technical concepts. These forms and expressions, almost only known to the professionals who receive them as part of their training, or copy them from law books, have developed into a highly technical language, characterized by its rigidly fixed formulae, or pre-fabricated routines, whose form has become part and parcel of their technical content. The legal text has thus acquired unique features which, in turn, bear heavily on its translation, defining the methods and techniques to be employed, and adding to the types of knowledge and skills required for the two steps of the process: comprehension of the source text and drafting of the target text. The first step requires deeper and more specific knowledge of the source language and its formal written varieties, which adds the skill of properly analyzing the text to uncover its meaning from within a highly complicated structure, with lengthy sentences and rare forms which stand as remote as possible from ordinary parlance. For the second step, full command of the target language and its formal style is required and supposed to be complemented by the ability to meticulously search in parallel texts for the appropriate target language prefabricated routines, normally used by experts in each type of legal texts.